Adam Smith as Bodhisattva? A metta analysis of global leadership. Issue 8 (8th September 2014) - Swierczek, Fredric William; Jousse, Dominique
Abstract : Purpose: – The purpose of this paper is to review approaches to Authentic Leadership and Mindfulness and to Global Competencies from the Buddhist perspective of Leadership Rajadhamma. It considers the parallel approach of Adam Smith's Moral Leadership. Design/methodology/approach: – The emphasis of this paper is a critique of the limitations of current teaching and practices in developing ethics and moral conduct in MBA programs and Global Leadership programs. Findings: – There is insufficient attention given to the Buddhist thought and practice of Leadership. Rajadhamma emphasizing the "Right Mind" and "Right Conduct." Because of his moral philosophy Adam Smith is offered as of an exemplar of Bodhisattva whom business executives would respect and emulate. Research limitations/implications: – This study is metatheoretical. The implications of this approach are to design Global Leadership Competencies with a greater emphasis on morality and ethical conduct. The practical wisdom of the Bodhisattva can provide a positive foundation for this design. Originality/value: – From the metatheoretical perspective the Theory of Moral Sentiments of Adam Smith has very interesting parallels with Buddhist practice in the twenty-first century with guidance for Global Leaders.